CARING KELUARGA DENGAN KUALITAS HIDUP LANSIA DI DUSUN STAN MAGUWOHARJO DEPOK SLEMAN - Purwandari, Andri; Handari, Murgi (POLITEKNIK KESEHATAN KARYA HUSDA YOGYAKARTA, 2024)
Background: Increasing life expectancy is an indicator of a nation's progress, but on the other hand it will cause many problems. This problem originates from the decline in physical and psychological functions due to the aging process. In these conditions, elderly people need help in carrying out their activities, both light help and help that is very dependent. Based on the Profile of the Yogyakarta Health Service, Yogyakarta Special Region, the number of elderly people in 2020 was 546,785 people. The family has a major influence on the physical and mental health of each family member. Families need to help the elderly to adapt themselves to the developmental tasks that must be carried out. Objective: Knowing the family's caring behavior towards the quality of life of the elderly. Methods: This research used a quantitative descriptive method with a cross sectional study approach, carried out at Stan Maguwoharjo Depok Sleman. The sample consisted of 65 elderly people using purposive sampling technique. Data were collected using a caring questionnaire and a quality of life questionnaire, with Chy Square Statistical Test analysis. Results:. The results of statistical tests obtained a p value of 0.285, which means that statistically there is no relationship between family caring and the quality of life of the elderly. Keywords: Caring for family, quality of life for the elderly.